(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In this study, deposition techniques and synthesis parameters are optimised in order to achieve the goal of increasing the critical current density (Jc) and critical temperature (Tc) of thin films made of Yttrium Barium Copper Oxide (YBCO). The thin films of YBCO, which are among the most widely used high-temperature superconducting materials, have a wide range of possible applications in the field of technology. Some of these applications include quantum computing, energy storage, and electronic devices. The microstructure and superconducting properties of films that have been deposited using various deposition techniques, such as magnetron sputtering, chemical vapour deposition (CVD), and pulsed laser deposition (PLD), will be investigated in this study. Additionally, the effects of substrate type, deposition temperature, oxygen pressure, and post-deposition annealing will also be investigated. The main objective of the research is to generate YBCO thin films that are optimised for use in high-efficiency superconducting devices. This will be accomplished by designing and developing these features.